2017
DOI: 10.7567/jjap.56.05da05
|View full text |Cite
|
Sign up to set email alerts
|

Group IV clathrates for photovoltaic applications

Abstract: Recent studies on type-II Si/Ge clathrates for photovoltaic (PV) applications are reviewed. The band-gap energies (Eg) experimentally estimated for Si and Ge clathrates are discussed on the basis of the comparison with theoretical calculation. For the Si and Ge clathrates, Eg = 1.7–1.9 and 0.6–0.8 eV are acceptable values, respectively. Thin films of type-II Si clathrates have been successfully synthesized on Si wafers. A device was fabricated using a Si clathrate thin film, and its PV response was observed. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Further repetition of the second annealing in vacuum tends to reduce the amount of Na. Some solutions using a cold plate 4 or iodine treatment 8,26 have been proposed to effectively reduce the amount of Na to negligible levels and this will represent a further improvement of the current work.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further repetition of the second annealing in vacuum tends to reduce the amount of Na. Some solutions using a cold plate 4 or iodine treatment 8,26 have been proposed to effectively reduce the amount of Na to negligible levels and this will represent a further improvement of the current work.…”
Section: Resultsmentioning
confidence: 99%
“…In the first case, the NaxSi136 type II binary clathrate structure presents semiconducting properties and is able to reach a 1.9 eV quasi-direct bandgap 7 . Furthermore the material presents the advantage of a direct bandgap as opposed to conventional diamond silicon 8 . In the second case, the large size of spheres composing the Si clathrates enables a high storage capacity within the cage that can be used for lithium or sodium ion batteries [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical calculations and experiments about electrical structure were performed on Si( cF 136), with the consensus that it has a wide optical band gap of 1.9 eV, approximately two-fold wider than 1.12 eV [ 19 , 62 ]. The photovoltaic response was observed in the Si( cF 136) film although short-circuit current, open-circuit voltage, and conversion efficiency were still not ideal (9.2 nA, 0.036 V, and 10 −5 %) [ 63 ]. Li et al [ 13 ] reported that the discharge capacity (181.2 mAh·g −1 at room temperature and 246.9 mAh·g −1 at 45 °C) is higher than the theoretical capacity of Si( cF 136) to form Na 24 Si 136 (168 mAh·g −1 ), which is attributed to the formation of fcc crystals ( Figure 3 b).…”
Section: Known Metastable Phases Of Siliconmentioning
confidence: 99%
“…4 Besides, Na4Si4 is a promising precursor for the synthesis of extended Si frameworks and allotropes of technological relevance. [5][6][7][8][9][10][11][12][13] NaxSi46 (x ≤ 8) and NaxSi136 (x ≤ 24) (type-I and type-II clathrates, respectively) consisting of Si cages encapsulating Na have been reported from Na4Si4 decomposition. [14][15][16][17] Empty Si46 and Si136 frameworks also provide tunable band gap for thermoelectrics and photovoltaics with Si136 exhibiting a quasi-direct bandgap of ~2 eV.…”
Section: Introductionmentioning
confidence: 99%